Evaluación periodontal en los estudiantes de sexo masculino de la modalidad de estudios presencial de la Universidad Nacional de Loja en el periodo mayo-julio 2014 - Herrera Parra, Segundo Israel (2014)
In accordance with the objectives of the study settled down to evaluate the periodontal state applying the index of necessity of periodontal treatment (INTPC) and the index of periodontal illness of Ramfjord (IEP) to the students of masculine sex. To identify the local factors that contribute to the bacterial badge accumulation: fixed aparatología, dental packing, and dental cavity. And to verify if it is present the factor of risk of periodontal illness: tabaquismo. The study is of traverse court - descriptive that was carried out in 442 students of masculine sex of the UNL, through the use of a clinical history that contains the data of the periodontal exam and the anamnesis. According to the results that they were applied in the (INTPC), it was obtained: code 0 43,4%, code 1 36,2%, code 2 17,7%, code 3 2,11%, code 4 0,6%. According to the (IEP) it was obtained: approach 1 31,67%, approach 2 30,31%, approach 3 1,13%, approach 4 19,45%, approach 5 0,45%, approach 6 0%, and they didn't present lost of insert 80,09%. Also as local factors: fixed aparatología 8,37%, decay dental 80%, dental packing 51,35%, and cigarette consumption in 41,18%. once it was obtained the results of the study, you concluded that the periodontal state in the students varies from the health to different grades of periodontal illness, present local factors that contribute to the bacterial badge accumulation being as: fixed aparatología of orthodontics, dental packing, decay dental, it is also present the factor of risk: tabaquismo. Key words: Periodontal illness, periodontal State, Bacterial Badge, insert Loss, dental Packing, Decay dental, Tabaquismo, Factor of Risk.